Ballistic impact response of complex concentrated alloys. (March 2022) - Muskeri, Saideep; Jannotti, Phillip A.; Schuster, Brian E.; Lloyd, Jeffrey T.; Mukherjee, Sundeep
Highlights: Ballistic performance of multi-principal element alloys evaluated. Failure mechanisms related to microstructural features. Single-phase alloys with equiaxed microstructure failed by ductile hole growth. Targets with lamellar microstructure showed brittle discing failure. Bimodal microstructure showed the best ballistic response due to high toughness. Abstract: The performance of complex concentrated alloys (or high entropy alloys) with widely varying microstructure is evaluated by ballistically impacting targets with spheres fired at normal incidence. By changing alloy composition in the Al-Co-Cr-Fe-Ni multi-principal system, the variation in microstructure included single-phase equiaxed grains, single-phase with bimodal grain-size distribution, and eutectic two-phase lamellar microstructure. Rigorous characterization in the form of bulk mechanical testing, scanning electron microscopy, and spatially resolved nano-indentation on initial and ballistically impacted plates was used to connect microstructural details to aspects of ballistic behavior governing performance. Based on the results, it was shown that although the addition of a harder secondary phase improves strength, cracks that initiate and propagate within the harder phase and ultimately across the target plate drastically reduce the ballistic performance of the two-phase material. The single-phase alloy with bimodal grain-size distribution exhibited superior ballistic performance compared to the other high entropy alloys, although none of these materials exceeded the performance of conventional rolled homogeneous armor steel. These results pave the way for development of high-performance concentrated alloys for ballistic applications by appropriate microstructural design. Graphical Abstract: Image, graphical abstract .